2019
DOI: 10.7717/peerj.6755
|View full text |Cite
|
Sign up to set email alerts
|

No association of COMT with insight problem solving in Chinese college students

Abstract: Genes involved in dopamine (DA) neurotransmission, such as the catechol-O-methyltransferase gene (COMT), have been suggested as key genetic candidates that might underlie the genetic basis of insight. In a sample of Chinese college students, this study examined whether COMT was associated with individual differences in the ability to solve classic insight problems. The results demonstrated that COMT was not associated with insight problem solving and there was no gender-dependent effect. This study, together w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…In their work it was shown that the COMT gene is associated with insight problem solving in men. Carriers of the Met allele demonstrated a significantly higher level of insight problem solving [31].…”
Section: Genetic Factors Associated With Other Cognitive Emotional Pmentioning
confidence: 95%
“…In their work it was shown that the COMT gene is associated with insight problem solving in men. Carriers of the Met allele demonstrated a significantly higher level of insight problem solving [31].…”
Section: Genetic Factors Associated With Other Cognitive Emotional Pmentioning
confidence: 95%